2003
DOI: 10.1128/jcm.41.6.2683-2685.2003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Epidemiologic Utility of Secondary Typing Methods for Differentiation ofMycobacterium tuberculosisIsolates

Abstract: Spoligotyping and mycobacterial interspersed repetitive unit-variable-number tandem repeat analysis (MIRU-VNTR) were evaluated for the ability to differentiate 64 Mycobacterium tuberculosis isolates from 10 IS6110-defined clusters. MIRU-VNTR performed slightly better than spoligotyping in reducing the number of clustered isolates and the sizes of the clusters. All epidemiologically related isolates remained clustered by MIRU-VNTR but not by spoligotyping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
56
2
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 12 publications
3
56
2
4
Order By: Relevance
“…Mycobacterial cultures were performed using liquid plus solid media at certified local laboratories. Isolates obtained at diagnosis and at the time of treatment failure or relapse underwent confirmatory drug-susceptibility testing (using solid media and the proportion method), DNA fingerprinting (20,21), and sequencing of the rpoB gene (22).…”
Section: Methodsmentioning
confidence: 99%
“…Mycobacterial cultures were performed using liquid plus solid media at certified local laboratories. Isolates obtained at diagnosis and at the time of treatment failure or relapse underwent confirmatory drug-susceptibility testing (using solid media and the proportion method), DNA fingerprinting (20,21), and sequencing of the rpoB gene (22).…”
Section: Methodsmentioning
confidence: 99%
“…The major advantage of rapid typing of isolates is the capacity to immediately provide a strain designation, which in turn may facilitate prompt public health intervention. While the technical feasibility of these methods has been well demonstrated (12,26), their public health utility remains to be determined.To date, studies of small outbreaks have shown that results from spoligotyping and MIRU-VNTR typing are often identical among isolates clustered by IS6110-based RFLP (6,7,8,11,15,16,18,23). However, the capacity of these modalities to provide unique patterns among unrelated isolates (i.e., their specificities) in a population-based study has not yet been evaluated.…”
mentioning
confidence: 99%
“…To date, studies of small outbreaks have shown that results from spoligotyping and MIRU-VNTR typing are often identical among isolates clustered by IS6110-based RFLP (6,7,8,11,15,16,18,23). However, the capacity of these modalities to provide unique patterns among unrelated isolates (i.e., their specificities) in a population-based study has not yet been evaluated.…”
mentioning
confidence: 99%
“…One comparison study has suggested that MIRU-VNTR typing may be more suitable for defining epidemiologically related isolates than are IS6110 typing and spoligotyping (16). Singapore is a Southeast Asian country with a heterogeneous population in which the majority is of Chinese origin and a substantial minority is of Indian origin.…”
mentioning
confidence: 99%